Risky Alcohol Consumption and Online Activity Levels. (6th December 2018) - Phillips, James G.; Landhuis, C. Erik; Ogeil, Rowan P.
ABSTRACT: University students engage in risky patterns of alcohol consumption, which may affect their health and performance at university. This study provides a novel analysis which tracked students' interaction with online course materials over time, and examined associations between online activity and alcohol related harm (as indicated by the Alcohol Use Disorders Identification Test). Study 1 tracked 63 undergraduate psychology students in the second half of a semester and found risky drinking behaviors were marginally related to reductions in online study activity. Study 2 tracked 88 undergraduate psychology students in the first half of a semester. Risky drinking behaviors were associated with less online activity after midday. Students reporting more alcohol related harm were less likely to login between 7 pm and midnight, and between 1 am and 6 am. This study demonstrates a potential sensitivity of online activity levels to alcohol use.